2013
DOI: 10.1007/s00383-012-3250-z
|View full text |Cite
|
Sign up to set email alerts
|

Wide variation in anal sphincter muscles in cases of high- and intermediate-type male anorectal malformation

Abstract: In both high and intermediate types of ARM, more than 2/3 of cases demonstrated unexpectedly displaced and deformed hypoplastic sphincters. Therefore, we recommend that variations in anal sphincter should be investigated on an individual basis prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It has been reported that the absence of an anus or perianal muscular complex may be a highly sensitive and specific marker that could be useful for the detection of anorectal atresia. However, previous reports have indicated that the muscular complex of the anus or anal canal may vary between the underdeveloped and normally developed stages; for example, the internal anal sphincter muscle is present in cases of high‐type anorectal atresia despite poor musculature development . According to Elchalal et al, a rudimentary external anal sphincter may be present in a few cases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the absence of an anus or perianal muscular complex may be a highly sensitive and specific marker that could be useful for the detection of anorectal atresia. However, previous reports have indicated that the muscular complex of the anus or anal canal may vary between the underdeveloped and normally developed stages; for example, the internal anal sphincter muscle is present in cases of high‐type anorectal atresia despite poor musculature development . According to Elchalal et al, a rudimentary external anal sphincter may be present in a few cases.…”
Section: Discussionmentioning
confidence: 99%
“…A completely nonvisualized anal structure is relatively easy to recognize on prenatal sonography, which indicates that the anal sphincter muscles are either aplastic or severely underdeveloped. However, muscular development may vary even in high‐type cases, 18 and small amounts of muscular components can be visible. Our 2 cases that were prenatally diagnosed as low‐type imperforate anuses but confirmed as high types showed a small hypoechoic anal ring and were therefore incorrectly diagnosed as low types.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all children with these anomalies require pelvic floor surgery in early childhood. In ARM patients, the pelvic floor is hypoplastic [1], and often a fistula is present from the rectum to perineum or to the urogenital tract. Associated anomalies are frequently of urogenital origin, such as hypospadias—present in 26 to 40% of the male ARM patients [2–4]—or of the internal reproductive system in females [5].…”
Section: Introductionmentioning
confidence: 99%